2022
DOI: 10.1016/j.isci.2021.103547
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular mechanisms underlying mangrove adaptations to intertidal environments

Abstract: Mangroves are halophytic plants belonging to diverse angiosperm families that are adapted to highly stressful intertidal zones between land and sea. They are special, unique, and one of the most productive ecosystems that play enormous ecological roles and provide a large number of benefits to the coastal communities. To thrive under highly stressful conditions, mangroves have innovated several key morphological, anatomical, and physio-biochemical adaptations. The evolution of the unique adaptive modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 253 publications
(470 reference statements)
0
21
0
2
Order By: Relevance
“…In the present study, a large number of KoWRKY genes were found to be constitutively expressed in the roots of K. obovata , with many of them, such as KoWRKY27 , KoWRKY28 , KoWRKY38 , KoWRKY39 , and KoWRKY49 , showing a tissue-specific expression pattern ( Figure 7A ), implying that KoWRKYs have vital functions in plant development and function differently in different tissues. K. obovata , a dominant mangrove species distributed along the southern coast of China, survives in harsh environments and experiences environmental stresses such as submergence, hypoxia, salinity, and even extremely low temperatures in winter ( Fei et al, 2021 ; Nizam et al, 2022 ). Hypoxia (which can be caused by submergence or waterlogging) and salinity stresses affect the survival and growth of many plants, some of which have developed multiple strategies to cope with these stressful conditions during their evolution, including morphological changes and scavenging of reactive oxygen species ( Tang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a large number of KoWRKY genes were found to be constitutively expressed in the roots of K. obovata , with many of them, such as KoWRKY27 , KoWRKY28 , KoWRKY38 , KoWRKY39 , and KoWRKY49 , showing a tissue-specific expression pattern ( Figure 7A ), implying that KoWRKYs have vital functions in plant development and function differently in different tissues. K. obovata , a dominant mangrove species distributed along the southern coast of China, survives in harsh environments and experiences environmental stresses such as submergence, hypoxia, salinity, and even extremely low temperatures in winter ( Fei et al, 2021 ; Nizam et al, 2022 ). Hypoxia (which can be caused by submergence or waterlogging) and salinity stresses affect the survival and growth of many plants, some of which have developed multiple strategies to cope with these stressful conditions during their evolution, including morphological changes and scavenging of reactive oxygen species ( Tang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not evidence for the occurrence of mangrove communities because of the absence of fossil representatives of known mangrove-forming trees and other mangrove associates. High percentages of Nypa pollen could be due to downstream transportation and further concentration in shallow marine environments or to expansions of Nypa palm populations, fostered by its above-mentioned invasion ability in coastal areas where the original vegetation has been removed (Numbere, 2019). In this case, increases in Nypa pollen in the fossil record could be linked to events of vegetation removal, probably by climatic changes or enhanced coastal erosion, but this is still too speculative in the present state of knowledge.…”
Section: The Oldest Caribbean Mangrovesmentioning
confidence: 97%
“…For example, N. fruticans was introduced over a century ago to the western African coasts (Niger Delta) to minimize coastal erosion and is now a major threat to native Rhizophora mangroves, which are receding due to anthropogenic disturbances such as oil exploration and urbanization. There, Nypa populations have been able to invade a variety of human-disturbed environments, from the outermost coastal fringe to the inner delta river channels (Numbere, 2019).…”
Section: Modern Caribbean Mangrovesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangroves are unique forested ecosystems that dominate the intertidal fringe of tropical and subtropical coasts worldwide and occupy a total of nearly 140,000 km 2 (Lugo & Snedaker, 1974;Bunting et al, 2018). Mangrove forests are usually dominated by a few mangroveforming tree species that provide the structural basis for the development of these characteristic ecotonal land-sea communities (Chapman, 1976;Tomlinson, 2016), which are instrumental in the maintenance of terrestrial and marine biodiversity and play a key role in the functioning of global biogeochemical cycles (Saenger, 2002;Nagelkerken et al, 2008;Nizam et al, 2022). Mangroves are highly sensitive to climatic changes, sea-level shifts and human pressure (Gilman et al, 2008;Spalding et al, 2014;Biswas & Biswas, 2019;Wang & Gu, 2021) and are currently among the world's most threatened ecosystems (Worthington et al, 2020).…”
Section: Introductionmentioning
confidence: 99%